2017
DOI: 10.1155/2017/4316316
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Glucose and Interleukin-1β Differentially Affect Retinal Microglial Cell Proliferation

Abstract: Diabetic retinopathy is considered a neurovascular disorder, hyperglycemia being considered the main risk factor for this pathology. Diabetic retinopathy also presents features of a low-grade chronic inflammatory disease, including increased levels of cytokines in the retina, such as interleukin-1 beta (IL-1β). However, how high glucose and IL-1β affect the different retinal cell types remains to be clarified. In retinal neural cell cultures, we found that IL-1β and IL-1RI are present in microglia, macroglia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 62 publications
2
25
0
2
Order By: Relevance
“…A study using the BV-2 cell line showed that a shift from normal glucose (5mM) to high glucose (25 mM) enhanced microglia proliferation, secretion of pro-inflammatory factors (TNF-α and oxygen radicals) and stress proteins including heat shock protein 70 (HSP70), heme oxygenase 1 (HO-1) and inducible nitric oxide synthase (iNOS) ( 56 ). In a separate study, high glucose levels increased the production of IL-1β in retinal cell culture, which induced microglia cell proliferation ( 57 ). As microglia cells continue to proliferate in the high glucose environment, they may reprogram their checkpoints and respond by secreting more inflammatory factors.…”
Section: Morphological Analysis Of Microglia In Animal Models and Patmentioning
confidence: 99%
“…A study using the BV-2 cell line showed that a shift from normal glucose (5mM) to high glucose (25 mM) enhanced microglia proliferation, secretion of pro-inflammatory factors (TNF-α and oxygen radicals) and stress proteins including heat shock protein 70 (HSP70), heme oxygenase 1 (HO-1) and inducible nitric oxide synthase (iNOS) ( 56 ). In a separate study, high glucose levels increased the production of IL-1β in retinal cell culture, which induced microglia cell proliferation ( 57 ). As microglia cells continue to proliferate in the high glucose environment, they may reprogram their checkpoints and respond by secreting more inflammatory factors.…”
Section: Morphological Analysis Of Microglia In Animal Models and Patmentioning
confidence: 99%
“…There are many works describing the microglial response to injury, activation mechanisms and phenotypes, and release of inflammatory mediators or their involvement in neurodegeneration and neuroprotection [ 27 33 ]. But little is known of their numerical and topographical dynamics and their correlation with the dying neurons, for instance, is the temporal and topographical course of PMC appearance regulated by the course of neuronal death?…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have demonstrated the role of microglia in the loss of retinal ganglion cells and endothelial dysfunction with subsequent BRB breakdown in diabetic retinopathy ( Krady et al, 2005 ; Gaucher et al, 2007 ; Zeng et al, 2008 ; Grigsby et al, 2014 ; Goncalves et al, 2016 ; Sorrentino et al, 2016 ) ( Figure 3 ). Upon exposure to high glucose levels, microglia become reactive and secret pro-inflammatory mediators namely, TNF ( Costa et al, 2012 ) and IL-1β ( Krady et al, 2005 ; Baptista et al, 2017 ). These cytokines induce the dysfunction of the BRB by enhancing caspase-3 activity in endothelial cells.…”
Section: Crosstalk Between Endothelial and Retinal Cellsmentioning
confidence: 99%